Integrating Realistic Mathematics Education (RME) in E-Comic Media: A Novel Approach to Foster Mathematical Creativity - Siswanto, Rizki Dwi; Kusumah, Yaya S; Dasari, Dadan; Juandi, Dadang; Hendriyanto, Agus; Bayuaji, Luhur (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to examine the effectiveness of integrating Realistic Mathematics Education (RME) into e-comic media for junior high school students in Jakarta in order to foster mathematical creativity and improve students’ ability to connect mathematical concepts with real-life situations. Methodology: This study employed a Research and Development (R&D) design using the ADDIE instructional model to develop RME-based e-comic media. The product was implemented with junior high school students in Jakarta, and data on mathematical creativity and learning responses were collected using creativity tests, questionnaires, classroom observations, and analyzed using descriptive and inferential statistics. Main Findings: The results indicate that RME-based e-comic media significantly improved students’ mathematical creativity across all indicators, including fluency, flexibility, originality, elaboration, and insight. Students showed higher learning motivation, more active engagement in discussions, and an increased ability to relate mathematical concepts to daily life, while teachers reported more dynamic classroom interactions, participation, and collaboration. Novelty/Originality of this study: This study introduces an innovative integration of Realistic Mathematics Education with interactive e-comic media to foster mathematical creativity in junior high school students. It advances mathematics education by demonstrating how context-rich, visually engaging digital narratives can transform conventional instruction into student-centered, creativity-oriented learning experiences and provides a scalable model for technology-enhanced, creativity-focused mathematics instruction.